The application of “scaffolding method” into promoting English learners' autonomy at an international school in Hanoi – An action research project - Nguyễn Thị Thảo Phương (2020)
Learner autonomy, a recurrent topic in language teaching over the last three decades, has been advocated from a pedagogical point of view and from the perspective of philosophy. Learner autonomy is one of the most important factors leading to the success in second language learning as well as life-long learning. In view of the necessity of learner autonomy in the context of the foreign language classrooms, the aim of this study is to foster autonomy of EFL learners in speaking skill by encouraging them to take the responsibility in the learning process. This is an action research conducted with 28 grade 10 English gifted students from class 10D at Global International School. The goal was achieved by raising their awareness, training them the necessary strategies, and applying proposed activities. After twelve lessons of implementing the action plan, questionnaire and was administered to discover the difference in the level of autonomy among the subjects. Other data collection instruments like follow-up interviews and classroom observations were also exploited to validate the results. The findings analyzed against a set of given criteria revealed that after having worked with this action plan, these learners were able to improve their autonomy as well as their spoken English. They became more aware of how certain aspects of language work and they were able to develop their self-confidence and stimulate their motivation to continue learning in class. This suggests a way of gauging students’ responsibility for their own learning and that learner autonomy, as a life-long mode of learning, can only be achieved with the efforts of both the teacher and the learner.